1972
DOI: 10.2467/mripapers1950.23.4_243
|View full text |Cite
|
Sign up to set email alerts
|

Unusually High Mean Sea Level in September 1971 Along the South Coast of Japan -1. Some Aspects of High Sea Level with Time Scale More Than One Week-

Abstract: High sea levels with time scale more than one week appear

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This is to say, what can we learn about the ocean climate beyond the shelf on time scales of days and longer from observing the properties of shelf and related coastal trapped waves near the coast? For example, can we detect accurately seasonal variations in the transport of the Gulf Stream (Mysak 1967a, Mysak '& Hamon 1969 or the Kuroshio (Isozaki 1972) fr om shelf-wave measurements? Can the theory of Gill & Clarke (1974) be used to measure variations in upwelling at the shelf break?…”
Section: Discussionmentioning
confidence: 99%
“…This is to say, what can we learn about the ocean climate beyond the shelf on time scales of days and longer from observing the properties of shelf and related coastal trapped waves near the coast? For example, can we detect accurately seasonal variations in the transport of the Gulf Stream (Mysak 1967a, Mysak '& Hamon 1969 or the Kuroshio (Isozaki 1972) fr om shelf-wave measurements? Can the theory of Gill & Clarke (1974) be used to measure variations in upwelling at the shelf break?…”
Section: Discussionmentioning
confidence: 99%
“…In September 1971, a UHSL event occurred at the south coast of Japan after the passage of a typhoon. Sea level anomalies (SLAs) exceeding 30 cm were observed and the high sea level state continued for about half a month (Isozaki 1972;Kurashige 1972;Miyazaki 1972). It was reported that positive SLAs propagated westward along the south coast of Japan and hence continental shelf waves were one possible cause of the UHSL in September 1971 (Isozaki 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Sea level anomalies (SLAs) exceeding 30 cm were observed and the high sea level state continued for about half a month (Isozaki 1972;Kurashige 1972;Miyazaki 1972). It was reported that positive SLAs propagated westward along the south coast of Japan and hence continental shelf waves were one possible cause of the UHSL in September 1971 (Isozaki 1972). Several UHSL events other than the UHSL in 1971 have also been reported by previous studies (Umeki 2003;Takagi et al 2008), in which contributions of CTWs and variations of the Kuroshio path to UHSL events in 2001 and 2006 have been discussed. In general, it is relatively easy to identify propagating sea level signals associated with CTWs using tide gauge observations.…”
Section: Introductionmentioning
confidence: 99%
“…That is, what can we learn about the ocean climate beyond the shelf on time scales of days and longer from observing the properties of shelf and related coastally trapped waves near the coast? For example, can we detect accurately seasonal variations in the transport of the Gulf Stream[Mysak, 1967a;Mysak and Hamon, 1969] or the Kuroshio[Isozaki, 1972] from shelf wave measurements? Can the theory ofGill and Clarke [1974] be extended to measure variations in upwelling at the shelf break?…”
mentioning
confidence: 99%